Recycling of coal bottom ash (CBA) as cement and aggregate replacement material: a review - Embong, R.; Kusbiantoro, A.; Muthusamy, K.; Ismail, N. (2021)
The construction sector is a significant contributor to greenhouse gas emissions that contribute to global warming. Therefore, utilizing ‘green and recycled by-products’ in construction is a measure towards a sustainable future. Coal Bottom Ash (CBA) generated from thermal power plants has increases in production. This causes disposal problems. However, due to the ongoing depletion of natural limestone in cement production and aggregate in construction, this material may be used as a recycled construction material. This paper presents a comprehensive analysis of CBA’s physical and chemical properties and the impact on the use of CBA as aggregate or cement. A small volume of CBA can substitute fine aggregates without compromising the strength of the concrete. Further research remains to be carried to explore the potential of this material in producing concrete with enhanced strength.